Vaginal Evisceration: An Unexpected Complication of Conization - Ali Ghassani; Benoit Andre; Caroline Simon-Toulza; Yann Tanguy le Gac; Alejandra Martinez; Fabien Vidal (Case Reports in Obstetrics and Gynecology)
Background. Large loop excision of the transformation zone (LLETZ) is routinely performed for the management of high grade intracervical neoplasia (CIN). Several uncommon complications have been described, including postoperative peritonitis, pseudoaneurysm of uterine artery, and bowel fistula. We report a unique case of postoperative vaginal evisceration and the subsequent management. Case. A 73-years-old woman underwent LLETZ for high grade CIN. On postoperative day 3, she was admitted for small bowel evisceration through the vagina. Surgical management was based on combined laparoscopic and transvaginal approach and consisted in bowel inspection and reinstatement, peritoneal washing, and dehiscence repair. Conclusions. Vaginal evisceration is a rare but potentially serious complication of pelvic surgery. This case report is to make clinicians aware of such complication following LLETZ and its management.